Dose-dependent effects of apple pectin on alleviating high fat-induced obesity modulated by gut microbiota and SCFAs - Yuanyuan Zhao; Jinfeng Bi; Jianyong Yi; Jian Peng; Qiancheng Ma (Food Science and Human Wellness)
Recently, pectin has been used as an alternative for commercial prebiotic products to modulate gut microbiota. In this study, the standard diet (Chow group) and high fat diet containing 0% (HF group), 1%, 3%, 5%, 8% or 12% (m/m) apple pectin (HF-P group) were offered ad libitum for 8 weeks to 4-week C57BL/6J mice (n = 10/group). Results showed that body weight gain (R2 = –0.990), subcutaneous adipose accumulation (R2 = –0.930), serum triglyceride elevation (R2 = –0.879), acetate (R2 = 0.955) and propionate concentration reduction (R2 = 0.985) were suppressed by pectin from 1% to 12%, indicating dose response to pectin consumption. Moreover, abundance of obesity-related bacteria Coriobacteriaceae, and pectin-degradating bacteria, Faecalibaculum, Ruminococcus were significantly increased with pectin dosage increased, and the R2 were 0.936, 0.963 and 0.937, respectively. Besides, attenuations for colonic injury and liver steatosis were observed after adding 5% and 8% pectin, respectively. This study confirmed the dose-sensitive manner of pectin to alleviate HF-induced obesity by modulating gut microbiota and enhancing short-chain fatty acids production.